2016
DOI: 10.1590/1982-027520160001000017
|View full text |Cite
|
Sign up to set email alerts
|

Práticas de leitura e compreensão de texto no 6º e 7º anos do ensino fundamental

Abstract: Resumo O objetivo deste estudo foi investigar as práticas de leitura de jovens adolescentes e sua relação com o desempenho na compreensão de textos. Participaram 121 estudantes do 6º e 7º anos do ensino fundamental de escolas públicas, com idades variando entre 11 e 14 anos, de ambos os sexos. Foram aplicados três instrumentos: o Questionário de Compreensão de Texto Cloze, o Teste de Compreensão de Leitura e o Questionário sobre Home Literacy. A partir disso, constatou-se que a maioria dos estudantes leem um o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…This type of treatment given to reading is one of the causes of the students' difficulties in performing activities that require reading comprehension, the lack of pleasure, and not developing the reading habits (Oliveira, Santos, & Rosa, 2016). Reading refers not only to educational content, but also to recreational reading, composed of a diversity of other materials provided in printed or digital media (Baptista et al, 2016). The study by Epçaçan and Damírel (2011) indicates that students with access to reading materials (e.g., newspapers, magazines) have stronger self-efficacy beliefs in this skill than students whose families do not have socioeconomic conditions to provide these resources for their children.…”
Section: Self-regulation Variables In the Reading Comprehensionmentioning
confidence: 99%
“…This type of treatment given to reading is one of the causes of the students' difficulties in performing activities that require reading comprehension, the lack of pleasure, and not developing the reading habits (Oliveira, Santos, & Rosa, 2016). Reading refers not only to educational content, but also to recreational reading, composed of a diversity of other materials provided in printed or digital media (Baptista et al, 2016). The study by Epçaçan and Damírel (2011) indicates that students with access to reading materials (e.g., newspapers, magazines) have stronger self-efficacy beliefs in this skill than students whose families do not have socioeconomic conditions to provide these resources for their children.…”
Section: Self-regulation Variables In the Reading Comprehensionmentioning
confidence: 99%
“…Uma vez bem desenvolvida, tende a favorecer o aprendizado dos diversos conteúdos ensinados na escola (Ferraz, Santos, & Cantalice, 2019;Oliveira, Santos, & Rosa, 2016). Além do inegável auxílio à instrução formal, a compreensão de leitura também pode proporcionar ao aluno momentos de diversão e lazer por meio da leitura recreativa (material não-didático como gibis e revistas) (Baptista, Freitas Junior, Peçanha, Soares, & Mettrau, 2016).…”
Section: Introductionunclassified
“…As for the studies that had elementary school students, we found researches directed at the early years (Borges & Santos, 2016;Bortolanza & Cotta, 2012;Carvalho, Monteiro, Alcará & Santos, 2013;Cunha & Santos, 2015;Gomes & Boruchovitch, 2011;Machado & Capellini, 2016;Mota et al, 2012;Mota & Santos, 2014;Oliveira, Santos, Boruchovitch & Rueda, 2012b;Suehiro & Santos, 2015;Witter & Silva, 2011), final years (Baptista et al, 2016;Joly & Piovezan, 2012;Joly et al, 2014;Oliveira et al, 2012a) and in both modalities (Oliveira et al, 2016). It is also noteworthy that among the reported studies, the study of reading comprehension was related to several variables such as gender, school year, type of school, writing skills, metatextual awareness, differential operation by Cloze test items, school performance, among others.…”
mentioning
confidence: 99%
“…The Cloze test was one of the instruments used by Baptista et al (2016) that evaluated the relationship between reading comprehension and reading practices of 121 students from the 6th and 7th grade. According to the results achieved, students that showed preference for pleasurable reading (comic books, manga and others) also underperformed in reading comprehension, while students who read school related content had better scores in interpreting texts.…”
mentioning
confidence: 99%